2014
DOI: 10.1007/s11010-014-2100-9
|View full text |Cite
|
Sign up to set email alerts
|

CD73-TNAP crosstalk regulates the hypertrophic response and cardiomyocyte calcification due to α1 adrenoceptor activation

Abstract: Cluster of differentiation 73 (CD73) is an ecto-5' nucleotidase which catalyzes the conversion of AMP to adenosine. One of the many functions of adenosine is to suppress the activity of tissue nonspecific alkaline phosphatase (TNAP), an enzyme important in regulating intracellular calcification. Since myocardial calcification is associated with various cardiac disease states, we studied the individual roles and crosstalk between CD73 and TNAP in regulating myocyte responses to the α1 adrenoceptor agonist pheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
4
15
0
Order By: Relevance
“…Here we analysed two different models of fibrosis: rapid-onset cardiac fibrosis induced by the hypertensive molecule Ang II, and chronic skeletal muscle fibrosis in the Sgca null mice. We confirm earlier evidence showing that TNAP is upregulated in tissue fibrosis (Herencia et al, 2015) (Gan et al, 2014), but also show here that the number of cells expressing TNAP increases in both heart and skeletal muscle. Furthermore, as the abrogation of TGF-β signaling in TNAP positive cells dramatically reduces vascular and interstitial fibrosis, we can conclude that TNAP is actively expressed in cells driving tissue fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…Here we analysed two different models of fibrosis: rapid-onset cardiac fibrosis induced by the hypertensive molecule Ang II, and chronic skeletal muscle fibrosis in the Sgca null mice. We confirm earlier evidence showing that TNAP is upregulated in tissue fibrosis (Herencia et al, 2015) (Gan et al, 2014), but also show here that the number of cells expressing TNAP increases in both heart and skeletal muscle. Furthermore, as the abrogation of TGF-β signaling in TNAP positive cells dramatically reduces vascular and interstitial fibrosis, we can conclude that TNAP is actively expressed in cells driving tissue fibrosis.…”
Section: Discussionsupporting
confidence: 92%
“…These effects are abolished by TNAP inhibition. This proves that the CD73 activity, and thus CD73-derived adenosine may act as endogenous negative regulators of hypertrophy and also calcification -possibly via inhibiting of TNAP [45].…”
Section: Cd73 and Arterial Calcificationsmentioning
confidence: 63%
“…There are also data on individual roles of CD73 and TNAP, as well as on the link between them, in the regulation of myocyte response to the a 1 -adrenoreceptor agonist-phenylephrine in the context of calcification and hypertrophy [45]. These studies clearly shows that cardiomyocyte hypertrophy in the response to phenylephrine is associated with TNAP stimulation and at the same time -CD73 inhibition, both in terms of expression and enzyme activity.…”
Section: Cd73 and Arterial Calcificationsmentioning
confidence: 97%
“…9 One of the many functions of adenosine is to suppress the activity of tissue nonspecific alkaline phosphatase, an enzyme important in regulating extracellular matrix calcification. 17 p.Arg463X is a nonsense mutation, so it will cause a truncated, and often nonfunctional protein product. By protein structural modeling, we showed that p.Gly454Arg in our family may influence the folding of β-pleated sheet and make the protein unstable, thus leading to an impaired CD73 enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%